Improving the Students’ Ability In Writing Recount Text Through Collaborative Task Writing on Facebook - Fuji Astuti; R. Bunga Febriani; Andi Rustandi (Jadila: Journal of Development and Innovation in Language and Literature Education, 2020)
This study focused on improving the students’ ability in writing recount text through collaborative task writing on Facebook. It was aimed at finding out how the teacher improves the students’ ability in writing recount text through collaborative writing on Facebook and figuring out the teacher and the students’ perceptions on the use of collaborative writing on Facebook in teaching and learning writing of recount text. This case study was conducted to the English teacher and 20 students at the tenth grade of a Senior High School in Kawali. Three instruments covering the observation, the interview, and the questionnaire were chosen to gain the data. The conversational analysis and the statistical techniques were used to analyze the data which were adapted from Dawson (2007, p. 123). The findings showed that the teacher improved the students’ ability in writing recount text through collaborative task writing on Facebook. The process of using collaborative writing on Facebook in teaching writing of recount text was implemented in ten steps. Those steps were quite similar with the steps proposed by Ahmed (2017, p. 149). The findings also showed that the use of collaborative writing technique on Facebook was beneficial for the teacher in teaching writing of recount text. The findings also showed that the students perceive positively on the use of collaborative task writing on Facebook in teaching and learning writing of recount text. It was concluded that the use of collaborative task writing on Facebook brings some benefits for the teacher and the students in teaching and learning writing of recount text. Therefore, the English teachers were suggested to encourage the students to implement collaborative writing on Facebook in teaching writing of recount text. Meanwhile, the students were also suggested to solve problems in learning writing of recount text by implementing collaboration writing technique on Facebook. In addition, the other researchers can use the result of this research in carrying out further studies.